1997
DOI: 10.1111/j.1460-9568.1997.tb01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drugs Inhibit a Gial 5‐Hydroxytryptamine Transporter in Rat Brain

Abstract: We assessed the role of glial cells in the uptake of serotonin (5‐hydroxytryptamine, 5‐HT). Primary cultures of rat and mouse cortical astrocytes took up and deaminated 5‐HT. The antidepressants citalopram, clomipramine, fluoxetine, fluvoxamine, paroxetine and sertraline inhibited this process. The presence of the mRNAs for the 5‐HT transporter and monoamine oxidase‐A (MOA‐A) was established in cultured astrocytes and in adult rat brain areas with (midbrain and brainstem) and without (frontal cortex) serotoner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 75 publications
3
18
1
Order By: Relevance
“…For one of our model systems, namely for primary astrocytes, evidence for functional SERT expression already exists, and we confirmed here results from earlier studies [30,31,33]. Although, the murine SERT promoter was found to be active in C6 glioma cells [42], to our knowledge, SERTspecific uptake had not previously been shown for our second model.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For one of our model systems, namely for primary astrocytes, evidence for functional SERT expression already exists, and we confirmed here results from earlier studies [30,31,33]. Although, the murine SERT promoter was found to be active in C6 glioma cells [42], to our knowledge, SERTspecific uptake had not previously been shown for our second model.…”
Section: Discussionsupporting
confidence: 90%
“…SERT-specific 5-HT uptake has been detected in primary astrocytes and various glial cells lines [10,29,30], but to our knowledge has not been reported for C6 glioma cells. Thus, we utilized saturation kinetics and various monoamine transporter inhibitors to characterize the high-affinity 5-HT uptake components in these cells.…”
Section: High-affinity 5-ht Uptake In C6 Glioma Cells Is Mediated By mentioning
confidence: 58%
See 1 more Smart Citation
“…Future study will be needed to elucidate the mechanism of glutamine in the effects of antidepressants. Second, the impairment of astrocytes may increase extracellular serotonin levels like antidepressant drugs because antidepressant drugs inhibit a glial serotonin transporter in the rat brain, increasing extracellular serotonin levels (Bel et al, 1997). It is likely that increases in extracellular serotonin levels remind us of selective serotonin reuptake inhibitor (SSRI) type of antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be said that there are presumably several subtypes of astroglial cells differing in specific protein expression, localization, and function which could explain these discrepancies (Halassa et al, 2007). In contrast, it has been shown that astrocytes in culture can take up serotonin and this can be blocked by SSRIs like fluoxetine (Bal et al, 1997; Inazu et al, 2001). It has therefore been speculated that astrocytes participate in the mode of action of this class of antidepressant drugs.…”
Section: Discussionmentioning
confidence: 99%